BIG DATA ANALYSIS USING ARTIFICIAL INTELLIGENCE AND ITS ROLE IN ENHANCING FINANCIAL TRANSPARENCY - Dr. Hayder Jameel Ahmed (Scholars Digest Publishing, 2025)
This study will examine the role of artificial intelligence in handling big data and its impact on enhancing corporate financial transparency. The study focuses on a sample of Iraqi banks listed on the Iraqi Stock Exchange during the period from 2014 to 2024. Two models were developed based on previous literature. The first model includes three main groups of indicators to measure the independent variable: managerial capabilities, technical capabilities, and tangible and intangible asset management. These groups comprise a total of ten sub-indicators. To assess the dependent variable—financial transparency—five main indicators were developed: governance, disclosure, investor confidence, timing of financial reports, and financial analysis. SPSS v27 was used to test the hypotheses. Our research findings concluded that the use of artificial intelligence to process the vast amounts of data that companies deal with helped improve the quantity and quality of information disclosed, thereby enhancing corporate financial transparency.
Keywords: Big data analysis - artificial intelligence- financial transparency- Financial accountability.